SUCCEEd: Um framework de suporte à criação e execução de workflows para SAS em ambientes IoT - Aragão Junior, Belmondo Rodrigues (2018)
The development of systems for the Internet of Things (IoT) environment generates the need to deal with characteristics such as self-adaptability and the dynamism of the environment. Hence, the traditional development approach, based on design-time decisions, can be counterproductive. Considering also the number of devices and technologies involved in IoT, this can cause an inability to deal with unforeseen scenarios at design-time. Therefore, the development of systems for IoT requires the use of practices that allow adapting the behavior and structure of the system more flexibly. Approaches based on models and structures that describe behavior, such as policies and workflows, have been proposed in the literature to achieve the capacity for self-adaptation. However, existing approaches do not fully support the core requirements of an IoT environment or are coupled to a specific environment and its technologies. Thus, this work proposes SUCCEEd, a support framework for the development of self-adaptive applications, in order to provide the creation and execution of sequences of adaptations in an IoT environment. To illustrate how SUCCEEd works, a proof of concept is implemented in the Android platform. In addition, simulated experiments related to coupling and the quality of self-adaptation are performed. The results indicate that (i) SUCCEEd has a high degree of reuse, (ii) the time used by SUCCEEd to provide the adaptation is less than the time used to perform the purpose of adaptation, and (iii) the number of steps required to provide adaptation is minimal in relation to time.